2018
DOI: 10.31254/jmr.2018.4306
|View full text |Cite
|
Sign up to set email alerts
|

Is Mean Platelet Volume to Platelet ratio a promising indicator of diabetic regulation in type 2 diabetes mellitus?

Abstract: Aims: Type 2 diabetes mellitus (T2DM) is associated with great disease burden since it has high prevalence, morbidity and mortality rates. Platelets (PLT) are directly or indirectly involve in the processes of chronic complications in T2DM. Beside serving as a marker of platelet activation, mean platelet volume (MPV) is also considered as an inflammatory indice. A MPV to PLT ratio (MPR) is introduced as a novel inflammatory predictor and a marker of worse outcome, recently. We aimed to study MPR levels of type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
9
1
Order By: Relevance
“…In addition, there was a significant and positive correlation between MPR with FPG and HbA1c. 20 In our study, no significant difference was observed between the three groups in terms of MPR. However, a positive correlation was observed between FPG and MPR in the diabetic group.…”
Section: Discussioncontrasting
confidence: 57%
“…In addition, there was a significant and positive correlation between MPR with FPG and HbA1c. 20 In our study, no significant difference was observed between the three groups in terms of MPR. However, a positive correlation was observed between FPG and MPR in the diabetic group.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, in the Sahbaz et al's study [24], PCT was the most powerful predictor of GDM in the second semester. MPR, a new indicator for predicting inflammation, is a sign of a bad outcome [28,29]. The results of the study conducted by Duman et al [28] showed that MPR levels were significantly higher in people with type 2 diabetes than in healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…MPR, a new indicator for predicting inflammation, is a sign of a bad outcome [28,29]. The results of the study conducted by Duman et al [28] showed that MPR levels were significantly higher in people with type 2 diabetes than in healthy individuals. This finding was consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…RPR) and the MPV/PLT ratio (i.e., MPR) are even more sensitive markers of atherosclerosis-connected risk [5,6], than RDW and PLT alone. Also, previous studies have shown an inflammatory and thrombotic predictive role of MPV, RDW, MPR, and RPR in many other diseases, such as obesity, type 2 diabetes, and hepatosteatosis [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%